Standardization Of Rendang Meat Recipes In Nagari Tiku Utara, Tanjung Mutiara District, Agam Regency - Agus Rianti; Wiwik Gusnita (Jurnal Pendidikan Tata Boga dan Teknologi, 2021)
The purpose of this study was to produce the best standardization of the recipe for rendang daging in Tanjung Mutiara Regency , Agam Regency to determine the ingredients and spices used, plating, processing techniques and 4 analysis of quality indicators which are expected to cover color, aroma, texture and taste. The background of the research is that there are spices used, processing techniques. Different processing techniques produce different quality indicators. This type of research is a mixed method. Sources of qualitative research data were obtained from 10 community experts in processing Rendang Daging and quantitative data sources were obtained from the community of 10 trained panelists who were experts in making Rendang Daging and 5 limited panelists from UNP Catering lecturers. Qualitative data collection techniques include observation, interviews, documentation while quantitative data collection techniques include the organoleptic test questionnaire format. Based on the results of the organoleptic test, it was found that the color quality indicators of chestnut rendang daging (brownish black), daging aroma  (fragrant spices), aroma (distinctive fragrant randang daging), daging texture (galiona erosa) (soft), the texture of the chestnut Rendang Daging (quite dry), the texture of the randang daging (quite crisp and quite brittle), the taste, the taste of the chest Rendang Daging (tasty).